2020
DOI: 10.3390/ijerph17239135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trunk Exercise on Unstable Surfaces in Persons with Stroke: A Randomized Controlled Trial

Abstract: Background: Improving balance-related ability is an important goal in stroke rehabilitation. Evidence is needed to demonstrate how this goal could be better achieved. Aim: Determine if trunk exercises on unstable surfaces would improve trunk control and balance for persons in the subacute stage of stroke. Design: An assessor-blind randomized controlled trial. Setting: Inpatients in the department of rehabilitation in a general hospital. Population: Patients who suffered a first-time stroke with onset from one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…Trunk control and balance ability was significantly improved which is in compliance with the present study result as depicted by TIS score 10 . Lee et al study (2020) conducted various type of trunk exercise on unstable surface and the result showed improvement in dynamic balance in post stroke patients 8 . The improvement in BBS score showed trunk training exercise is highly effective to achieve balance in post stroke survivor which is correlated to the studies conducted in 2016 in Spain 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trunk control and balance ability was significantly improved which is in compliance with the present study result as depicted by TIS score 10 . Lee et al study (2020) conducted various type of trunk exercise on unstable surface and the result showed improvement in dynamic balance in post stroke patients 8 . The improvement in BBS score showed trunk training exercise is highly effective to achieve balance in post stroke survivor which is correlated to the studies conducted in 2016 in Spain 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Postural sway seen after stroke while preserving sitting/standing position as well as when shifting the body's center of mass in smaller range 8 . Neurologically, trunk is the key point of control for body movement so trunk stability is required for the distal movement.…”
Section: Introductionmentioning
confidence: 99%
“…They found that trunk stabilization training had a beneficial effect on the trunk function and balance in standing positions and mobility in patients after a stroke [22]. The results of the stability studies indicate that in patients after strokes, trunk stabilization exercises should be introduced [23][24][25][26]. Lee et al assessed the influence of breathing exercises on trunk control, assuming that the trunk muscles play a large role in the work of the respiratory system [27].…”
Section: Introductionmentioning
confidence: 99%
“…( 23 ) There is evidence that trunk training exercises showed moderate evidence to improve trunk performance and dynamic sitting balance. ( 24 26 )…”
Section: Introductionmentioning
confidence: 99%
“…(23) There is evidence that trunk training exercises showed moderate evidence to improve trunk performance and dynamic sitting balance. (24)(25)(26) Though the existing studies proved that trunk exercises were mediated by improved trunk control, the gap still limits the understanding of lower limbs for balance. The current study hypothesized that PNF neck pattern and trunk-specific exercise would significantly improve trunk control and balance.…”
Section: Introductionmentioning
confidence: 99%